Deficiencies among French Learners in Primary, Secondary, and High Schools in the Analamanga Region - Antananarivo, Madagascar - Andrianiaina Solo Raivo Lyh Raphaël; Andrianarimanana Jean Claude Omer; Andrianjary Myriam; Rakotoson Olivia; Rasoloarivony Theis Lala; Fidelio Arnold Ulrich; Ratiarimananjatovo Narindra; Ratsimandisa Haritiana Zo; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2024)
The present study highlights French language acquisition in primary, secondary, and public high schools in Antananarivo and its surrounding areas. Classroom observations and surveys were conducted in two public primary schools (EPP 67 ha Nord-Est and EPP Antanimena Est), two General Education Colleges (CEG Betsimitatatra and CEG Antanimena), and three public high schools (Lycée Moderne Ampefiloha, Lycée Analamahitsy, and Lycée Ivato). Field research reveals factors contributing to students' language deficits: lack of exposure, with 60.41% of students using French exclusively in school and during French classes. This leads to language deficiencies stemming from limited practice and vocabulary, observed in 43.13% of students, indicating incomplete mastery of the French language. Consequently, the majority (42.40%) resort to using dictionaries due to this vocabulary gap. Analysis of learning methods shows that most students encounter challenges across all subjects (78%), with a preference for memorization as the primary strategy (63.33%). Additionally, the majority believes that the use of visual aids is the most effective method to address their shortcomings (71.81%). Therefore, this study focuses on observing French language learning methods and aims to enhance them for more satisfactory outcomes.